Human Umbilical Cord Blood Mononuclear Cells Ameliorate CCl4-Induced Acute Liver Injury in Mice via Inhibiting Inflammatory Responses and Upregulating Peripheral Interleukin-22 - Zhang, Jinming; Zhai, Hengben; Yu, Pei; Shang, Dabao; Mo, Ruidong; Li, Ziqiang; Wang, Xiaolin; Lu, Jie; Xie, Qing; Xiang, Xiaogang (Frontiers in Pharmacology, 2022)
Background: Human umbilical cord blood mononuclear cells (hUCBMNCs) show therapeutic effects on many inflammatory diseases. The deterioration of acute liver injury is attributed to excessive inflammatory responses triggered by damage-associated molecular patterns (DAMPs) and pathogen-associated molecular patterns (PAMPs). Whether hUCBMNCs treatment is a promising strategy for acute liver injury/failure needs to be investigated. Methods: Liver injury mice induced by PAMPs, DAMPs, or DAMPs plus PAMPs were developed. DAMPs included CCl4 (carbon tetrachloride), APAP (acetaminophen), and ConA (Concanavalin A). PAMPs included Klebsiella pneumoniae (K.P.) and Salmonella typhimurium (S. Typhimurium). DAMP plus PAMP-induced liver injury was developed by sequential CCl4 and K.P. administration. hUCBMNCs were injected intravenously. Results: hUCBMNCs significantly prolonged mice survival time in DAMP plus PAMP-induced liver failure but had no benefit in bacteria-infected mice. hUCBMNCs significantly alleviated hepatic necrosis post CCl4/ConA insult. In CCl4-induced acute liver injury, peripheral levels of interleukin (IL)-22 were upregulated and liver regeneration was enhanced after treating with hUCBMNCs at 48h. The levels of p62 and LC3B-II, autophagy markers, were also upregulated in the hUCBMNC-treated group. Conclusion: hUCBMNCs as a kind of cell therapeutic strategy could attenuate acute liver injury in mice, which is executed by enhancing autophagy and regeneration in the liver via inhibiting inflammatory responses and upregulating peripheral IL-22.